2016
DOI: 10.1186/s12906-016-1147-4
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal attributes of major phenylpropanoids present in cinnamon

Abstract: BackgroundExcessive production of free radicals has been implicated in many diseases including cancer. They are highly reactive and bring about oxidation of biomolecules i.e., proteins, lipids and nucleic acids which are associated with many degenerative diseases. Natural products acting as antioxidants have ability to neutralize free radicals and their actions and hence they mitigate their harmful effects. The present study was designed to investigate pharmacological properties viz., antioxidant, antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 50 publications
2
34
0
1
Order By: Relevance
“…Our observation agrees with the previous results of antitumor activity of the ethanolic extract of B. variegata extract against Dalton's ascetic lymphoma (DAL) in Swiss albino mice [93] and in N-notrosodiethylamine induced experimental liver tumour in rats and human cancer cell lines [94]. Our findings are also in agreement with the previous results of many herbal drugs such as alcoholic extract of Thuja occidentalis [95], aqueousmethanol (3:7) extract of Boerhaavia diffusa [96], methanolic extract of Withania somnifera roots [97], naturally occurring allyl and phenyl isothiocyanates [98], curcumin [99], sulphorafane [100], B. variegata leaf extract [101], Piper longum against A549 cell line [102], Cinnamaldehyde and eugenol [103] etc. have been reported to inhibit metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Our observation agrees with the previous results of antitumor activity of the ethanolic extract of B. variegata extract against Dalton's ascetic lymphoma (DAL) in Swiss albino mice [93] and in N-notrosodiethylamine induced experimental liver tumour in rats and human cancer cell lines [94]. Our findings are also in agreement with the previous results of many herbal drugs such as alcoholic extract of Thuja occidentalis [95], aqueousmethanol (3:7) extract of Boerhaavia diffusa [96], methanolic extract of Withania somnifera roots [97], naturally occurring allyl and phenyl isothiocyanates [98], curcumin [99], sulphorafane [100], B. variegata leaf extract [101], Piper longum against A549 cell line [102], Cinnamaldehyde and eugenol [103] etc. have been reported to inhibit metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Results at Table (3) showed significant improve of feed conversion ratio in basil, fennel, cinnamon, oregano and mixture treatments by 5.6, 5.6, 6.2, 7.7 and 9.2% respectively, compared to the control group. These results may be due to the ability of these herbs on the reactive and bring about oxidation effect of bio-molecules of proteins, lipids and nucleic acids which are associated with many degenerative diseases (Sharma et al, 2016). There were gradually satisfactory while insignificant decreasing in feed intake by (4.2,3.6,3.1,3.0 and 0.8%) for cinnamon, basil, fennel, oregano and mixture treatments, respectively, compared to the control group (Table 3).…”
Section: Broilers Performancementioning
confidence: 99%
“…Cinnamon , Cinnamomum Zeylanicum (Lauraceae) have principle components cinnamaldehyde possessed metal ion chelating lipo-protective, antibacterial and anti-proliferative activities (Erdogru et al, 2003), antiinflammatory (Han and Parker 2017) and have eugenol acting as antioxidant (Pandey et al, T 2012) which acting with cinnamic acid and cineol component to neutralize free radicals to hence they mitigate their harmful effects indicating their usefulness in food and pharmaceutical sector (Sharma et al, 2016) as well as provides protection against allergens causing atherosclerosis (Nayak et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamomum belongs to genera of Lauraceae family that includes many species with different properties and commonly used as spices in food or as fragrances. Furthermore some of these species are used in traditional medicine and, relatively to species parthenoxylon, it has been demonstrated that the extract of the bark has antioxidant effects [49]. Several constituents of cinnamomum species have cytotoxic and apoptotic activities on various cancer cell lines [50].…”
Section: Lignans Isolated From Plantsmentioning
confidence: 99%